Acompañamiento docente como estrategia para mejorar el rendimiento académico - Aguilar Cumbe, Priscila Alexandra; Lima Cuchimbo, Kevin Anthony (Machala, Utmachala, 2023)
This degree project is used based on the budgets established by the Degree System of the Technical University of Machala, prior to obtaining the degree of Bachelor of Education Sciences: Basic Education Mention. Which is based on the collection of accurate and updated information on teaching support strategies that will allow raising academic performance in students in the second year of Basic General Education; with a qualitative- quantitative approach, using techniques such as the interview with teachers, the student survey and the observation guide, which allowed the evidence to be systematized based on the proposed objective, where the sample to be analyzed was twenty-six students and two second-grade teachers. year of Basic General Education at the Victoria Cañarte School. The titling project was developed with the diagnosis of the object of study, the teaching accompaniment as a strategy to improve academic performance, due to the fact that students with low understanding of the contents taught are currently observed, being considered a high-impact problem that It has been evidenced in the School of Basic General Education "Victoria Cañarte" of the Canton El Guabo. Consequently, the variables corresponding to teaching support and academic performance were also delimited, subsequently the theoretical, conceptual and legal framework was developed. Faced with what was investigated and analyzed, it was possible to conclude that teachers do not apply accompaniment strategies in the classroom, which is why students obtain a low understanding of the contents and therefore low academic performance. Likewise, it was possible to observe the disinterest of the student in learning, the lack of communication between teacher and student, and the low participation in the classroom. In conclusion, in view of what was observed, a seminar workshop on accompaniment strategies was proposed as a proposal, which favors, guides and benefits teachers and students who have difficulties solving tasks in class, who have little understanding, and little interest in the classroom. In this way, it is intended to promote classroom development and improve the educational quality offered at the Victoria Cañarte School.
El presente proyecto de titulación esta empleado en base a los presupuestos establecidos por el Sistema de Titulación de la Universidad Técnica de Machala, previo a la obtención del título de Licenciados en Ciencias de la Educación: Mención Educación Básica. El cual está basado en la recolección de información precisa y actualizada sobre las estrategias de acompañamiento docente que permitirán elevar el rendimiento académico en los estudiantes de segundo año de Educación General Básica; con un enfoque cuali- cuantitativo, empleando técnicas como la entrevista a los docentes, encuesta a los estudiantes y la guía de observación, que permitieron sistematizar las evidencias en función del objetivo planteado, donde la muestra a analizar fueron veintiséis estudiantes y dos docentes de segundo año de Educación General Básica de la Escuela Victoria Cañarte. El proyecto de titulación se desarrolló con el diagnóstico del objeto de estudio, el acompañamiento docente como estrategia para mejorar el rendimiento académico, debido a que en la actualidad se observa estudiantes con baja comprensión de los contenidos impartidos, siendo considerado un problema de alto impacto que se ha evidenciado en la Escuela de Educación General Básica “Victoria Cañarte” del Cantón El Guabo. Por consiguiente, también se delimitaron las variables correspondientes al acompañamiento docente y el rendimiento académico, posteriormente se desarrolló el marco teórico, conceptual y legal. Frente a lo investigado y analizado se logró concluir que los docentes no aplican estrategias de acompañamiento dentro del aula, es por ello que los estudiantes obtienen una baja compresión de los contenidos y por ende un bajo rendimiento académico. Así mismo se pudo observar el desinterés del alumno por aprender, la falta de comunicación entre docente y discente, y la escasa participación dentro del aula de clase. En conclusión, frente a lo observado se planteó como propuesta un seminario taller de estrategias de acompañamiento, que favorezca, guie y beneficie a docentes y alumnos que presentan dificultades para resolver tareas en clase, que tienen poca comprensión, y poco interés dentro del aula, de esta manera se pretende propiciar el desarrollo áulico y mejorar la calidad educativa que se brinda en la Escuela Victoria Cañarte.
Keywords: ACOMPAÑAMIENTO DOCENTE; RENDIMIENTO ACADEMICO; ESTUDIANTE; ESTRATEGIA; ESCUELA